226k views
2 votes
I would appreciate it if I could get a step-by-step on how to solve this problem. Thank you.!

I would appreciate it if I could get a step-by-step on how to solve this problem. Thank-example-1
User Sidon
by
6.2k points

1 Answer

2 votes

Answers: -2,
(x+4)/(3), -1

Step-by-step explanation:

Inverse is when the x's and y's are swapped.

g(x) = (-4, 8), (-2, 9), (4, 7), (9, -1)

g⁻¹(x) = (8, -4), (9, -2), (7, 4), (-1, 9)

g⁻¹(9) = ??? when x = 9, what is y? Answer: -2

*******************************************************************

h(x) = 3x - 4

To find the inverse, let y represent h(x). Then swap the x's and y's and solve for y:

x = 3y - 4

+4 +4

x + 4 = 3y


(x+4)/(3) = y

h⁻¹(x) =
(x+4)/(3)

*******************************************************************

h(-1) = 3(-1) - 4

= -3 - 4

= -7

h⁻¹(h(-1)) = h⁻¹(-7)

h⁻¹(-7) =
(-7+4)/(3)

=
(-3)/(3)

= -1

User Vital
by
5.9k points